Interactive simulation of finite element equation processing for educational purposes - Lee, Jae Young (Computer applications in engineering education, 2015)
This article introduces the educational functions of a computer program developed and put into practice for the computer‐aided instruction of the finite element method. An interactive simulation with graphical visualization is used as a tool to teach and learn the concepts and procedures related to the construction and solution of finite element stiffness equations. The tool encompasses the stages of processing finite element equations from element modeling to equation solving. Any operation of this educational tool is not an emulation of computational processes, but an actual execution of finite element processing. Thus, instructors of the finite element method may use this educational program as a tool to present complex computational aspects in comprehensible graphic images. Students may experience and explore each stage of the computation using the interactive simulation, and attain a better understanding of the concepts and procedures of the stiffness method, bypassing manual calculation or computer programming. The instructional tool has been implemented as a part of a finite element analysis program. © 2013 Wiley Periodicals, Inc. Comput Appl Eng Educ 23:157–169, 2015; View this article online at wileyonlinelibrary.com/journal/cae; DOI 10.1002/cae.21586